SIKAP DAN ETIKA DALAM MENGHADAPI IKHTILAF PENDAPAT MAZHAB FIQIH - Muhammad Zuhdi dan Faisal (Hukum Keluarga Islam IAIN LANGSA, 2019)
Dissent is a common thing, it even becomes sunnatullah or human nature. In thedevelopment of Islamic law, Ikhtilaf (differences of opinion) regarding the establishment of lawhas occurred among the Companions of the Prophet. When the Apostle was still alive, butdifferences of opinion could soon be reconciled by returning to the Messenger of Allah. Amongfriends after the Prophet's death often arise differences of opinion in establishing the law oncertain matters. Dissent in the tradition of Islamic scholars is not new. Countless works havebeen written by special Islamic scholars to study, compare, and then discuss different views withtheir respective arguments. The attitude of the Companions of the Prophet when facingdifferences among them, the attitude of the Imams mazhab of the Muslim, the wise and wiseattitude in addressing the disputes between them.